Документи представництва Західноукраїнської Народної Республіки у Франції 1919-1923 рр. (з колекції Центрального державного архіву громадських об'єднань України) - Власенко, С. (Краєзнавство, 2018)
У статті подається огляд документів із фонду № 269 «Колекція документів “Український музей
в Празі”» Центрального державного архіву громадських об'єднань України, що стосуються участі
делегації Західноукраїнської Народної Республіки в Паризькій мирній конференції 1919-1920 рр. та
подальшої міжнародної діяльності західноукраїнських дипломатів у Франції до березня 1923 р. The article provides a review of documents of Central State Archives of Public Organizations of Ukraine’s
fonds № 269 «A Collection of Documents of Ukrainian Museum in Prague» concerning the participation of
West Ukrainian People’s Republic’s delegation in Paris Peace Conference, 1919-1920 and Western Ukrainian
diplomats’ further international activities until March 1923. It describes the types of the documents, analyzes
their content, and comprises a compilation of some of them. The complex of documents is divided into two
groups: the first ones constitute the documents of the period of the Paris Peace Conference from January
1919 to January 1920; the second group presents the documents of the Western Ukrainian delegation in
Paris from February 1920 to March 1923. The most commonly presented type of documents, correspondence
of statesmen of the Western Ukrainian People’s Republic, is described. The documents recreate the course
of negotiations in Paris, traced the relationship between individual members of the Western Ukrainian
delegation and their attempt to use that international situation to protect the sovereignty and territorial
integrity of the Western Ukrainian People’s Republic. Copies and text of separate documents from the
collection «Ukrainian Museum in Prague» were submitted. В статье представлен обзор документов из фонда № 269 «Коллекция документов “Украинский
музей в Праге”» Центрального государственного архива общественных объединений Украины, которые
касаются участия делегации Западноукраинской Народной Республики в Парижской мирной конферен-
ции 1919-1920 гг. и дальнейшей международной деятельности западноукраинских дипломатов во Фран-
ции до марта 1923 г.